2004
DOI: 10.1242/jcs.01207
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adipocyte differentiation by mechanical stretching through ERK-mediated downregulation of PPARγ2

Abstract: Furthermore, the differentiation inhibited by the stretching was also restored by synthetic PPARγ ligand. Collectively, these results suggest that the inhibition of adipocyte differentiation in response to stretching is mainly attributable to the reduced expression of PPARγ2, which is mediated by activation of the ERK/MAPK system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
119
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 41 publications
10
119
2
1
Order By: Relevance
“…However, only SAPK/ JNK activation reversed TGZ-induced PPAR␥ activity. In previous studies, a number of signaling effectors, including MAPK family members, have been shown to phosphorylate PPAR␥ (41)(42)(43). PPAR␥ phosphorylation can affect its activity, including reduction in the sensitivity of PPAR␥ to its cognate ligands or affect its translocation or transactivation activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, only SAPK/ JNK activation reversed TGZ-induced PPAR␥ activity. In previous studies, a number of signaling effectors, including MAPK family members, have been shown to phosphorylate PPAR␥ (41)(42)(43). PPAR␥ phosphorylation can affect its activity, including reduction in the sensitivity of PPAR␥ to its cognate ligands or affect its translocation or transactivation activity.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Hyperplasia appears primarily in the commitment stages in adipose tissue development and is caused by the proliferation and differentiation of mesenchymal stem cells into preadipocytes. 46,47 Hypertrophy occurs as the result of excessive accumulation of triglycerides during the process of differentiation from preadipocytes to mature adipocytes. 48 Therefore, evo may reduce hyperplasia and hypertrophy in fat tissue through an induced inhibition of both adipocyte number and size.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the phosphorylated form of the other MAPK pathway effector we observed, ERK1/2, as well as an epistatic component of the pathway (c-Raf) suggests that this pathway is active in mammary fat tissue. Signaling by the ERK pathway is reportedly involved in adipocyte cellular responses to cell size sensing (113), presence of adipokines (114,115), and differentiation (116,117). Consequently activity of this pathway in mammary fat tissue is consistent with a normal physiological cycle in adipocyte growth and development.…”
Section: Tgf-␤/smadmentioning
confidence: 92%